Checklist and new distribution records of katydids (Orthoptera: Tettigoniidae) from Colombia - Chamorro-Rengifo, Juliana; Cadena-Castañeda, Oscar J.; Braun, Holger; Montealegre-Z., Fernando; Romero, Rodrigo I.; Marquez, Francisco Humberto Serna; Gonzales, Ranulfo (Zootaxa, 2011)
This article compiles information about the species of Tettigoniidae present in Colombia, based on biological collections and the literature. To date 345 species grouped in 129 genera and seven subfamilies are known from the country. The presence of 77 species recorded from other countries is documented for the first time. Regarding the katydids the data on geographical distribution show that less than 50% of the national territory has been scientifically explored. The best-represented area is the Valle del Cauca, due to regional faunistic inventories and taxonomic studies.